Comparison of the cytotoxicity of bisphenol A and its analogs on human placental BeWo cells - Kim, Mi Jin; Jo, Ah-Ra; Kim, Ji-Young; An, Mi-Jin; Shin, Geun-Seup; Lee, Hyun-Min; Kim, Jinho; Park, Jinhong; Kim, Chul-Hong; Kim, Jung-Woong (Molecular & cellular toxicology, 2023)
Background Bisphenol A (BPA) and its alternatives (BPF, BPS) are widely used in daily consumer products, which commonly expose humans to these chemicals. Bisphenols (BPs) are endocrine-disrupting chemicals widely present in the environment and can accumulate in the entire food chain by circulating in the ecosystem. In humans, BPs intake leads to accumulation in the human body and causes many chronic diseases, including endocrine disruption, immunotoxicity, and cancer. Objective Although several studies have demonstrated the negative effect of BPA and its alternatives, studies have yet to be determined whether bisphenols can affect human trophoblast cells. Thus, this study aimed to analyze the toxic effect of BPs on the human trophoblast cell line BeWo. Results We investigated the cytotoxic effect of BPs on human trophoblast cells. The cytotoxicity was measured by the MTS assay and flow cytometric analysis that representing the cell viability, cell proliferation, cell cycle progression and apoptotic cell death. BPs had no effect on BeWo cell viability at concentrations below 100 mM, and did not cause significant changes in cell proliferation and apoptosis. However, BPA and BPS altered cell cycle progression and checkpoint regulator expression. Conclusion BPs did not affect cell viability and proliferation. However, BPS altered the G 0 /G 1 and G 2 /M phases of the trophoblast BeWo cells by increasing cyclin B1 expression.